Cryogenics on the stratospheric terahertz observatory (STO). Issue 1 (November 2015) - Mills, G; Young, A; Dominguez, R; Duffy, B; Kulesa, C; Walker, C
Abstract: The Stratospheric TeraHertz Observatory (STO) is a NASA funded, Long Duration Balloon experiment designed to address a key problem in modern astrophysics: understanding the Life Cycle of the Interstellar Medium. STO surveys a section of the Galactic plane in the dominant interstellar cooling line at 1.9 THz and the important star formation tracer at 1.46 THz, at ∼1 arc minute angular resolution, sufficient to spatially resolve atomic, ionic, and molecular clouds at 10 kpc. The STO instrument package uses a liquid helium cryostat to maintain the THz receiver at < 9 K and to cool the low noise amplifiers to < 20 K. The first STO mission (STO-1) flew in January of 2012 and the second mission (STO-2) is planned for December 2015. For the STO-2 flight a cryocooler will be added to extend the mission lifetime. This paper discusses the integration of the STO instrument into an existing cryostat and the cryogenic aspects of the launch and operation of the STO balloon mission in the challenging Antarctic environment.